Considerações gerais sobre prótese fixa adesiva - Jorge, Janaína Habib [UNESP]; Neppelenbroek, Karin Hermana; Campanha, Nara Hellen; Segalla, José Claudio Martins [UNESP]; Giampaolo, Eunice Terezinha [UNESP] (My University, 2011)
The success rate of resin-bonded fixed partial dentures is directly related to the adhesive system and the tooth preparation design for good retention. These resin-bonded bridges represent a prosthodontic alternative, based on their costeffectiveness, conservative techniques, and ease of laboratory manufacturing. Through a thorough review of the literature, this study aimed to report on cavity designs, types of materials used, and the advantages and disadvantages of the resin-bonded fixed partial denture. One of significant advantages of the resin-bonded fixed partial dentures is the conservation of the tooth structure, whereas its main disadvantage includes aesthetic limitations, given that the alloy may in fact be visible. Preparation design, cement type, and casting alloy type, as well as surface treatment, are among the factors that influence the longevity of resin-bonded fixed partial dentures. Treatments with resin-bonded fixed partial dentures present a bright outlook regarding the conservation of tooth structures, as well as a high level of success.

O sucesso das próteses fixas adesivas está diretamente relacionado ao sistema adesivo utilizado e ao tipo de preparo realizado para obtenção de uma boa retenção. Essas próteses surgiram como uma alternativa protética, tendo em vista o baixo custo, o uso de uma técnica mais conservadora e a facilidade laboratorial. Este estudo objetivou discutir, por meio de uma revisão de literatura, as formas de preparo, os tipos de materiais e as vantagens e desvantagens do uso de próteses fixas adesivas. Dentre as principais vantagens, destacase a conservação da estrutura dentária e como desvantagem, a limitação da estética devido à possibilidade do aparecimento da liga metálica. O desenho do preparo, o tipo de cimento e o tipo de liga, bem como o tratamento de superfície são alguns dos fatores que podem influenciar na longevidade do manuseio desse tipo de prótese. O tratamento com próteses fixas adesivas tem grande potencial na conservação dos dentes pilares e também um percentual significativo de sucesso.
General considerations on resin-bonded fixed partial denture
Keywords: Resin-Bonded; Tooth preparation prostodontic; Dental abutments; Prótese adesiva; Preparo prostodôntico do dente; Dente suporte